DEBT FINANCING AND PROFITABILITY OF MANUFACTURING FIRMS IN NIGERIA - Cecilia Adurayemi, Adu,; Matthew Idowu, Abimboye, (International Journal of Multidisciplinary Reseach, 2026)
The paper examined the effect of debt financing on the profitability of manufacturing firms in Nigeria while the specific objective assessed the relationship between debt-equity ratio and the return on equity of manufacturing firms in Nigeria. Data were obtained from five manufacturing firms listed on the Nigerian Exchange Group from 2004 to 2023. Regression analysis using E-view was adopted in this procedure to carry out the analysis. It was found out that ROE and debt to EBITDA ratio have non-significant Jarque-Bera statistics, with p-values of 0.190 and 0.690 respectively, suggesting that these variables may be considered approximately normally distributed. It was recommended that firms should focus on improving their interest coverage and earnings capacity, as these were positively related to financial performance and can improve a firm's creditworthiness and financial flexibility.